Sistem Deteksi Gas Pintar Berbasis IoT dan Terintegrasi Fuzzy-Logic untuk Keamanan Distribusi Gas secara Realtime - Azizah, Putri Nur; Taqwa, Ahmad; Salamah, Irma (Building of Informatics, Technology and Science (BITS), 2025)
Abstract−LPG gas is a widely used fuel for daily needs in households, industry, and commercial sectors. Although easy to use and affordable, LPG contains highly flammable compounds that can cause fires and explosions, especially if leaks go undetected. Field surveys show that most gas agents or depots still use manual methods relying on the sense of smell to detect gas leaks. This approach does not provide optimal or accurate results, making it ineffective and potentially harmful to health when excessive gas is inhaled. Therefore, this research aims to design a gas leak detection system based on the Internet of Things (IoT) using the Fuzzy Tsukamoto algorithm integrated with the Blynk application. The method involves the design of hardware and software using three sensors as input parameters: MQ-6 (gas), DHT22 (temperature), and Flame Sensor (fire), which are processed by the ESP32 microcontroller through fuzzy logic rules. The system outputs include a visual LED indicator, buzzer activation, status display on the LCD, notifications via Blynk, and automatic fan response to neutralize the gas. Based on results simulation and testing under three environmental condition scenarios, the system is able to detect gas leaks with average error of 0.315% and accuracy of 90.55%. This study demonstrates a reliable, effective, and responsive gas leak detection system. It is expected that the system can minimize the potential dangers of gas leaks and enhance gas storage safety.